Plan de exportación para la comercializar sacos de lana de la empresa Kichwa Maki en Minneapolis-Minnesota - Ruíz, Luis D. (2019)
The purpose of this research work was to design an export plan for the Kichwa Maki company from the city of Cotacachi towards the US market, in a process of internationalization of woolen bags and at the same time progressively improve its commercialization, in addition this export plan served as a guide to follow where information on export processes and documents is consolidated. The export plan proposed the direct export of wool bags, that is, it was not going to depend on third parties to develop the export of its products, which allowed the company to generate a competitive advantage. This export plan mainly helped to improve the marketing and production of woolen bags, in the same way to open more sources of employment and improve the quality of life of the people who work for the company and its owners and will contribute to the textile development of the canton. The methodology used for the realization of this export plan was that of John Daniels, who establishes the steps and processes to develop a successful export, in addition to making a diagnosis of the company in which it allowed to perform an internal and external analysis in which Strategies were established to increase their strengths, in addition to conducting a market study where they could select the ideal country for export.